2021
DOI: 10.1155/2021/7197224
|View full text |Cite|
|
Sign up to set email alerts
|

The Effect of Introducing Infographic Pattern on Developing Cognitive Understanding by Using AI Technology for University Students during the COVID-19 Pandemic

Abstract: During the COVID-19 pandemic, this study sought to determine the impact of AI-supported infographic templates (static versus animated) on academic achievement, visual thinking skills, and willingness to learn among a sample of university students. The researcher created two distinct AI-supported instructional infographic templates to determine the effect of such an independent variable on his three other primary dependent variables, namely, academic accomplishment, visual thinking skills, and willingness to le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Table 4 summarizes the papers analysed, including information about the AI applied, who used the AI, and what main benefits it provided. In brief, the results revealed that the main advantages of AI applications in higher education were to improve educational outcomes [3,7,12,16,18,22,27,29,30,32], to enhance institutional decision-making [1,8,14,21,26], and to advance institutional systems [2,10,23]. Moreover, the end users benefiting from the AI applications mainly were higher education institutions (n=11), instructors (n=9), and college students (n=6).…”
Section: Advantages and Disadvantages Of Using Aimentioning
confidence: 99%
“…Table 4 summarizes the papers analysed, including information about the AI applied, who used the AI, and what main benefits it provided. In brief, the results revealed that the main advantages of AI applications in higher education were to improve educational outcomes [3,7,12,16,18,22,27,29,30,32], to enhance institutional decision-making [1,8,14,21,26], and to advance institutional systems [2,10,23]. Moreover, the end users benefiting from the AI applications mainly were higher education institutions (n=11), instructors (n=9), and college students (n=6).…”
Section: Advantages and Disadvantages Of Using Aimentioning
confidence: 99%
“…In addition, the session also covered some basic concepts on how to use infographic design tools, including online tools like Canva ® , to help students create their infographics. The 12 tips shared with the students included: (1) identifying the target audience; (2) establishing the infographic's purpose; (3) crafting an engaging title for the target audience; (4) selecting clear and concise information; (5) effectively connecting graphical elements to tell a story; (6) emphasising the main ideas; (7) creating an initial draft of the infographic; (8) following basic principles of graphic design; (9) selecting appropriate colours; (10) testing the infographic to ensure optimal performance; (11) checking for possible typos; and (12) developing an efficient dissemination plan. In addition, in this session, teachers highlighted the importance of using evidence-based health information to create the infographic.…”
Section: Design and Description Of The Learning Strategy Innovationmentioning
confidence: 99%
“…From an educational perspective, the use of infographics has shown its efficacy as a useful pedagogical tool in higher education teaching [6][7][8][9][10][11]. Previous studies have emphasised infographics as a pedagogical tool in the teaching of languages [12], mathematics [13,14], science [6], and technology [15], among other disciplines.…”
Section: Introductionmentioning
confidence: 99%
“…For the students, it was clear that the infographic task facilitated learning about public health and the overall experience was received as positive (Shanks et al, 2017). Besides, over undergraduate students, infographics has a favourable impact on academic accomplishment, visual thinking skills, willingness to learn (Samra, 2021) and allow undergraduate students to delve into the study topics of a subject (Malik & Nakhla, 2020). Despite the multiple possibilities and uses of infographics in different educational contexts, there are no studies that have specifically assessed the usefulness of infographics to facilitate learning of pharmacology as a subject for the Nursing Degree.…”
Section: Introductionmentioning
confidence: 99%